Sustaining and enhancing local and organic agriculture: assessing consumer issues in New Hampshire. Issue 1 (2nd January 2016) - Pyburn, Maria; Puzacke, Kyle; Halstead, John M.; Huang, Ju-Chin
ABSTRACT: This article presents results of a study assessing consumers' local and organic fresh produce purchasing habits in New Hampshire, including willingness to pay estimations, determining the consumers' definition of local, consumers' perceptions of local and organic fresh produce, and identifying demographic trends. This study aims to provide growers with consumer information that may help with crop selection, growing technique selection, and pricing. It will also provide awareness into the possible opportunity for agricultural growth in New Hampshire communities.